Software models for relays. - McLaren, P.G.
This paper reviews the past and present uses of relay models. It discusses the various types of models, what information is required to build such models and the model validation process. Examples of present and possible future use of software models are given
Keywords: EMTP; Computer simulation; Model validation process; Power system relay protection; Relay software models